2022
DOI: 10.12968/ippr.2022.12.3.45
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and changes with COVID-19: Canadian paramedics' experiences

Abstract: Background: Healthcare systems, practitioners and communities have experienced momentous change and strain because of the COVID-19 pandemic. Although paramedics are an essential component of the public health emergency response, the literature has focused primarily on the views of physicians, nurses and hospital administrators. Aims: This research sought to improve the understanding of the lived experiences of paramedics throughout the initial stages of the COVID-19 outbreak. Methods: The perspectives of param… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 24 publications
0
0
0
Order By: Relevance
“…The challenges of directing personnel and particularly continuous communication, as well as constantly changing guidelines, were highlighted as a significant factor in reducing paramedics' well-being during the pandemic's early stages. International studies found similar results among paramedics [3,4,[6][7][8][9]20] and extensive literature reviews among healthcare personnel in general [21,22]. The constant, excessive, sometimes poor-quality, multichannel communication was challenging to follow and caused frustration and uncertainty among paramedics in already unclear circumstances.…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations
“…The challenges of directing personnel and particularly continuous communication, as well as constantly changing guidelines, were highlighted as a significant factor in reducing paramedics' well-being during the pandemic's early stages. International studies found similar results among paramedics [3,4,[6][7][8][9]20] and extensive literature reviews among healthcare personnel in general [21,22]. The constant, excessive, sometimes poor-quality, multichannel communication was challenging to follow and caused frustration and uncertainty among paramedics in already unclear circumstances.…”
Section: Discussionmentioning
confidence: 79%
“…Challenges in managing the work environment were evident, such as the lack of support provided by supervisors to personnel, downplaying the seriousness of the situation, or neglecting to take personnel into consideration. Similar experiences have led to declines in well-being in international studies as well [4][5][6][7][8][9][10]. Supervisors' working hours during the pandemic were likely consumed by administrative challenges and ensuring sufficient personnel resources, leaving them with little time to support personnel.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations